Microwave assisted synthesis of nanocomposites in Zn-Sn-O-Ag system and their photocatalytic activity. Issue 1 (9th March 2015) - Grabis, J; Letlena, A; Rasmane, Dz; Krumina, A
Abstract: The crystalline Zn2 SnO4 Zn2 SnO4 /Ag and ZnO-Zn2 SnO4 nanoparticles with specific surface area in the range of 24.1-28.5 m 2 /g were prepared by combining microwave assisted synthesis with additional calcination at 900 °C. The parameters of the powders were compared with those of ZnO and ZnO/Ag nanoparticles prepared by microwave synthesis at 150 °C. The crystallite size of oxide and silver nanoparticles was in the range of 30-52 nm and 18-60 nm, respectively, depending on composition. The prepared nanoparticles showed high photocatalytic activity in degradation of methylene blue under ultraviolet and sunlight irradiation.